2014
DOI: 10.1212/wnl.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

The PRO-ACT database

Abstract: Objective: To pool data from completed amyotrophic lateral sclerosis (ALS) clinical trials and create an open-access resource that enables greater understanding of the phenotype and biology of ALS.Methods: Clinical trials data were pooled from 16 completed phase II/III ALS clinical trials and one observational study. Over 8 million de-identified longitudinally collected data points from over 8,600 individuals with ALS were standardized across trials and merged to create the Pooled Resource Open-Access ALS Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
212
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(225 citation statements)
references
References 42 publications
11
212
1
1
Order By: Relevance
“…Nevertheless, similar to our prior analysis,16 to gain insight into potential benefit and plan for a future trial, participants from the Pooled Resource Open‐Access ALS Clinical Trials (PRO‐ACT) dataset18, 19 and the ceftriaxone trial (dataset provided by the Northeast ALS Consortium)20 served as historical controls. The PRO‐ACT dataset contains open‐access ALS Functional Rating Scale revised (ALSFRS‐R) and survival data for over 10,723 participants from 23 Phase 2 and 3 ALS trials conducted between 1990 and 2013, including the ceftriaxone cohort 18, 19, 21. The large data volume collected under controlled environments justifies its use as a noncontemporaneous historical dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, similar to our prior analysis,16 to gain insight into potential benefit and plan for a future trial, participants from the Pooled Resource Open‐Access ALS Clinical Trials (PRO‐ACT) dataset18, 19 and the ceftriaxone trial (dataset provided by the Northeast ALS Consortium)20 served as historical controls. The PRO‐ACT dataset contains open‐access ALS Functional Rating Scale revised (ALSFRS‐R) and survival data for over 10,723 participants from 23 Phase 2 and 3 ALS trials conducted between 1990 and 2013, including the ceftriaxone cohort 18, 19, 21. The large data volume collected under controlled environments justifies its use as a noncontemporaneous historical dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Progression Inverse association [22][23][24] Inverse association [25][26][27][28] No association [29,30] Inverse association in HD, MSA, MCI [31][32][33] Laboratory…”
Section: Urate and Its Determinants Are A Risk Factor For Neurodegenementioning
confidence: 99%
“…Higher urate levels are associated with slower clinical progression in Huntington's disease, multiple system atrophy, and mild cognitive impairment [29][30][31]. In ALS, most [25][26][27][28] but not all [32,33] studies found urate to represent a prognostic factor for survival. The reasons for these conflicting results in ALS are not completely clear and may be related to methodological differences, variable sample size, and a modest effect size.…”
Section: Urate and Its Determinants Are Molecular Predictors Of Diseamentioning
confidence: 99%
“…Urate, the end‐product of human purine metabolism, is an endogenous antioxidant10, 11 and proposed neuroprotectant12, 13, 14, 15 and its levels may be increased by edaravone treatment 6, 16. High urate levels correlate with improved survival in ALS epidemiologic studies17, 18, 19, 20, 21, 22, 23 and with favorable outcomes in other neurodegenerative diseases, most notably Parkinson's disease (PD) 24, 25, 26. Further, urate is neuroprotective in several models of neurodegeneration 12, 27, 28, 29, 30, 31, 32…”
Section: Introductionmentioning
confidence: 99%